2007
DOI: 10.4161/cc.6.11.4278
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B and Cyclin A Confer Different Substrate Recognition Properties on CDK2

Abstract: The transitions of the cell cycle are regulated by the cyclin dependent protein kinases (CDKs). The cyclins activate their respective CDKs and confer substrate recognition properties. We report the structure of phospho-CDK2/cyclin B and show that cyclin B confers M phase-like properties on CDK2, the kinase that is usually associated with S phase. Cyclin B produces an almost identical activated conformation of CDK2 as that produced by cyclin A. There are differences between cyclin A and cyclin B at the recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 42 publications
4
78
0
Order By: Relevance
“…CDK4/cyclin D3 and T160pCDK2/cyclin A or T160pCDK2 (100 ng unless otherwise stated) were mixed with 5 g of substrate (Histone H1, GST-RbCT, or GST-p107spacer), 0.1 mM ATP, 1 Ci [ 32 P]␥-ATP, 5 mM MgCl2, 50 mM Tris⅐HCl (pH 7.5) (final volume 10 L) at 20°C. After 7.5 min, the reactions were stopped by the addition of SDS and samples were analyzed by SDS/PAGE and autoradiography (32). p27 Kip1 was included as appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CDK4/cyclin D3 and T160pCDK2/cyclin A or T160pCDK2 (100 ng unless otherwise stated) were mixed with 5 g of substrate (Histone H1, GST-RbCT, or GST-p107spacer), 0.1 mM ATP, 1 Ci [ 32 P]␥-ATP, 5 mM MgCl2, 50 mM Tris⅐HCl (pH 7.5) (final volume 10 L) at 20°C. After 7.5 min, the reactions were stopped by the addition of SDS and samples were analyzed by SDS/PAGE and autoradiography (32). p27 Kip1 was included as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Human CDK1, CDK4, and cyclin D3 were all expressed in insect cells. CDK1 was expressed as a GST fusion and purified as described (32). CDK4 and cyclin D3 were cloned into pFastBac1 (Invitrogen) with, respectively, GST and PreScission protease recognition sequences and a FLAG tag at the amino terminus, and they were coexpressed in Sf-9 cells and purified by exploiting the CDK4 GST tag.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, knockdown of Gpr19 affected progression through the cell-cycle at a later stage, namely in G 2 -M. This conclusion is based on 2 independent lines of evidence, namely the determination of DNA content by flow cytometry and the quantification of the G 2 -M marker cyclin B1 and the mitosis marker phosphorylated histone H3 by immunocytochemistry. Cyclin B1 exerts its function in conjunction with cyclin-dependent kinase 1 during late G 2 -phase and early mitosis (44). Histone H3 phosphorylation at Ser10 correlates with chromosome condensation during mitosis with phosphorylation levels starting to increase in late G 2 -phase (45).…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] Very recently, two studies have reported the structures of cyclin B. [43][44] To begin with, we examine the crystal structure of cyclin A2 41 to establish the structural framework for peptide binding. This reveals an overall fold characterized by two a-helical domains (Fig.…”
Section: Introductionmentioning
confidence: 99%